(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the methodological foundations and modern approaches to human capital development in the context of globalization and socio-economic transformation. The study analyzes theoretical perspectives on human capital, highlights key methodological principles, and explores contemporary strategies aimed at enhancing human potential. Special attention is given to education, innovation, and lifelong learning as core components of sustainable human capital development. The research emphasizes the importance of an integrated and interdisciplinary approach in formulating effective policies and practices for human capital growth.